Measurement-driven optimal control of utility-scale power systems: A New York State grid perspective. (February 2020) - Mukherjee, Sayak; Babaei, Saman; Chakrabortty, Aranya; Fardanesh, Bruce
Highlights: An optimal control design on a transmission-level model of the New York state grid. PMU-only design without knowing the full-scale transmission model. Tools from data analytics, system identification and control theory are used. Techniques are engineered to improve the dynamic performance of NYS power grid. Bridges the gap between the design advancements and the implementation opportunities. Abstract: This paper focuses on designing and testing a supplementary controller for an ultra-large, utility-scale power system, namely the New York State (NYS) Power Grid from a completely measurement-based perspective. We present the control design using the Flexible AC Transmission System (FACTS) facility at the NYS grid. We use the utility-scale Eastern Interconnection (EI) model consisting of over 70, 000 buses in the PSS/E platform for this research. The coherency structure of the NYS grid is analyzed by performing Principal Component Analysis (PCA) on frequency measurements obtained from multiple contingency simulations. Thereafter, we use the frequency measurements from PMU-enabled buses to identify a reduced-order state space model of the grid such that it matches the input-output characteristics along with identifying the inter-area modes. This model is then used to design the Linear Quadratic Gaussian (LQG) based optimal FACTS controller. Then the controller is implemented in the PSS/E model of the Eastern Interconnection (EI) as a PSS/E-FORTRAN based user defined module. The effectiveness of the control performance is shown using the non-linear simulations under different contingencies provided by the New York Independent System Operator (NYISO).